Constitutional court rejection on omnibus law: How to understand after submission - Sibuea, Hotma P. (Linguistics and Culture Review, 2021)
The purpose of this legal and constitutional study was to deeply understand the causes and impacts of rejection of the ratification of the Omnibus Bill and its derivatives of the Job Creation Bill by demonstrators consisting of students and laborers throughout Indonesia. To make it easier for us to understand the above problems, we have carried out a series of data collections since the Omnibus Bill was discussed until it was passed by Parliament and rejected by demonstrators. For data, secondary legal information in the form of legal publications, textbooks, journals, and court decisions related to the Omnibus Law and other information in the form of articles published in the mass media has also been used as data. Finally, we can conclude that the findings include: Several laws originating from the Omnibus law have legitimized environmental destruction, ignoring customary rights that are more environmentally friendly and sustainable. The majority of the Omnibus Law committee comes from the elite who do not think about the civilian element, including the new law derivative people.